ANALISIS GAYA BAHASA DAN NILAI SOSIAL BUDAYA KUMPULAN ESAI MEN COBLONG KARYA OKA RUSMINI SEBAGAI BAHAN PEMBELAJARAN SASTRA - Noval Hadi Pangestu; I Nyoman Diarta; I Komang Widana Putra (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
The objectives of this study are to: (1) describe the language style used by the author in Oka Rusmini's collection of Men Coblong Essays; (2) describe the socio-culture contained in Oka Rusmini's collection of Men Coblong essays; The method used in this research is an empirical method. The empirical method of research which is solely based on existing facts and also phenomena that are empirically alive in the speaker, so that what is produced or recorded is a description of the language which is usually said to be like a portrait: exposure as it is, in In this research, the document in question is the collection of Men Coblong Essays by Oka Rusmini. The data source in this study is the collection of Men Coblong Essays by Oka Rusmini published by Grasindo publication in 2019. The data collection technique used in this study is the note-taking technique, because the data is in the form of text. The steps in data collection are as follows: (1) reading Oka Rusmini's collection of Men Coblong Essays repeatedly; (2) record sentences that state the use of language and socio-cultural styles. The data analysis technique used in this study used a flow analysis model which included three components, namely: 1) data reduction; (2) data presentation; (3) drawing conclusions. Based on the results of the study, it is concluded that: (1) the language styles contained in Oka Rusmini's collection of Men Coblong essays are: Personification, Parable, Hyperbole, Metonomia, Metaphorical Language, Euphemistic Language; (2) socio-culture contained in the collection of Men Coblong Essays by Oka Rusmini, namely: caring, courtesy, sacrifice, independence, discipline, purity of the heart of faith.